Penegakan Hukum Polres Sumedang dalam Menangani Perkara Kecelakaan Lalu Lintas di tinjau dari Pasal 235 UU No 22 tahun 2009 tentang Lalu Lintas dan Angkutan Jalan - Hardani; Budi Sujati (Institut Agama Islam Negeri Kerinci, 2019)
Data on traffic accidents collected by Sumedang Regional Police in 2014 as well as from daily observations provide an illustration that the level of traffic safety and the level of public compliance with traffic laws and regulations is very alarming, this is if strategic steps are not taken to improve the level of safety and improvement of community legal compliance will not only cause loss of life, but will also cause economic losses. So to realize legal certainty in traffic, Law Number 22 of 2009 concerning Traffic and Road Transportation Article 235 was formed.The two factors that influence the implementation of Law Number 22 Year 2009 include: (1). External factors such as substantive legal substance, lack of personnel and many personnel violating professional discipline and ethics, limited police facilities and infrastructure, changes and developments in Sumedang Regency. (2). Internal factors such as the Sumedang Regional Police made an effort to propose to revise the Traffic Law, increase the number of personnel, budget support had been allocated up to the police station level, build a toll road, conduct morning malls, and grow public legal awareness.The results of the study concluded that the enforcement of traffic law at the Sumedang Regional Police Station had not been fully implemented and was not effective enough. Because the responsibility of traffic accidents is not based on Article 235 of Law Number 22 Year 2009 concerning Traffic and Road Transportation and the high number of traffic accidents in Sumedang Regency.